DIVERSITY OF LEPIDOPTERAN INSECTS OF PACHAIMALAI HILLS, TIRUCHIRAPPALLI DISTRICT, TAMIL NADU - PAVITHRRA DHARANI, S. K.,; KATHIRVELU, C.,; . KANAGARAJAN, (The Bioscan, 2019)
To document the lepidopteran diversity of selected localities of Pachaimalai hills, Tamil Nadu, a preliminary survey was made from January to December, 2015. During the survey, the diversity of lepidopterans was recorded by using aerial netting, light trapping and host rearing methods. The results showed that a total of 984 lepidopterans were observed, out of which, 230 butterflies, 32 skippers and 722 moths. The collected/observed lepidopterans were diagnosed up to subfamily level by using taxonomic keys. Nine superfamilies were recorded under the suborder Glosatta, among them, Noctuoidea was found dominant with 312 individuals followed by Papilionoidea (230). Under Papilionoidea, Nymphalidae was predominant with 78 numbers followed by Pieridae (69), Papilionidae (54) and Lycaenidae (29) while the superfamily Hesperioidea found with one family Hesperiidae (32). Eight families consisting moth insects were noticed, in which, Noctuidae (312) was found superior followed by Crambidae (208), Geometridae (56), and Oecophoridae (42). Out of 24 subfamilies identified, Spilomelinae was found to be superior with 112 numbers followed by Noctuinae (111). The diversity of lepidopterans depend on the presence of host plant resources as indicated by the individuals recorded under the families like Noctuidae and Crambidae, which has wide host range.